Serum decorin and biglycan levels as predictive biomarkers for lung fibrosis severity and mortality risk in COVID-19 patients - Ahmad, Shaaf; Maqsood, Kaleem; Liaqat, Farwa; Roohi, Nabila (Frontiers in Medicine, 2025)
IntroductionIndividuals experiencing severe symptoms of COVID-19 are at the greatest risk of developing post-COVID lung fibrosis, which significantly impacts long-term health outcomes. This study aims to investigate the predictive potential of serum biomarkers, specifically decorin and biglycan, in assessing the severity and mortality risk among COVID-19 patients.MethodsFor this study, healthy controls and COVID-19 patients (n = 240) among them 186 with moderate and 54 with severe symptoms from Ittefaq Hospital and Mayo Hospital, Lahore, Pakistan were recruited satisfying the inclusion and exclusion criteria. Patients were followed up for 2 months. Serum level of decorin and biglycan was evaluated by ELISA. One-way ANOVA and Independent sample “t”-test were applied at significance level p < 0.05 by using GraphPad Prism.ResultsDecorin levels significantly decreased from controls (43.36 ± 1.14 ng/mL) to moderate (40.24 ± 0.64 ng/mL) and severe COVID-19 patients (35.49 ± 1.00 ng/mL) (p = 0.0059). Biglycan levels increased from controls (66.15 ± 2.22 pg/mL) to moderate (70.02 ± 1.57 pg/mL) and severe patients (75.88 ± 1.97 pg/mL) (p = 0.0042). In follow-up, survivors had higher decorin (39.6 ± 0.59 ng/mL) than non-survivors (35.84 ± 1.61 ng/mL) (p = 0.0319). Biglycan levels were similar between survivors (70.98 ± 1.41 pg/mL) and non-survivors (73.99 ± 3.24 pg/mL) (p = 0.459). Higher decorin levels correlate with survival in COVID-19 patients.ConclusionSerum decorin and biglycan levels are valuable biomarkers for predicting severity and mortality in COVID-19 patients. Lower decorin and higher biglycan levels correlate with increased disease severity, emphasizing their potential to identify patients at risk for lung fibrosis and guide clinical management.